Myasthenia Gravis and Associated Diseases - Tanovska, Nikolina; Novotni, Gabriela; Sazdova-Burneska, Slobodanka; Kuzmanovski, I; Boshkovski, Bojan; Kondov, Goran; Jovanovski-Srceva, Marija; Kokareva, Anita; Isjanovska, Rozalinda (Scientific foundation SPIROSKI, 2018)
BACKGROUND: Myasthenia gravis (MG) is an autoimmune disease caused by the action of specific antibodies to the postsynaptic membrane of the neuromuscular junction, leading to impaired neuromuscular transmission. Patients with MG have an increased incidence of other autoimmune diseases. AIM: to determine the presence of other associated diseases in patients with MG.METHOD: A group of 127 patients with MG followed in 10 years period, in which the presence of other associated diseases has been analysed.RESULTS: The sex ratio is in favour of the female sex, the average age of the initial manifestation of the disease is less than 50 years, 65.4% of the patients with MG have another disease. 15.0% patients have associated another autoimmune disease. Thyroid disease is the most common associated with MG, rarely rheumatoid arthritis (RA), systemic lupus erythematosus (SLE) and other autoimmune diseases. Other diseases include hypertension, heart disease, diabetes, respiratory diseases, dyslipidemia. 10.2% of the patients are diagnosed with extrathymic tumours of various origins. CONCLUSION: Associated diseases are common in patients with MG, drawing attention to the possible common basis for their coexistence, as well as their impact on the intensity and treatment of the disease.
Keywords: myasthenia gravis; autoimmune disease; associated condition; thymus; tumor; thymectomy